“It’s real. It’s a thing:” Mental health counselors’ listening exhaustion during COVID-19 - Damla Ricks; Grace Ellen Brannon (Qualitative Research in Medicine & Healthcare, 2023)
Mental health counselors regularly use active listening skills to be present with each client; however, active listening may cause burnout due to high emotional labor, inadequate staffing, excessive workload, and many other issues, each of which contributes to career exits. COVID-19 exacerbated all of these factors, and—adding to already stressful conditions—most mental health professionals were forced to conduct therapy sessions via telehealth. For this study, twenty licensed mental health counselors at various stages of their careers were interviewed during the height of the pandemic to understand their experiences with the technology and other factors related to their workload during that time. Thematic qualitative analysis was used to explore effects of active listening—including requisite adjustments made for virtual therapy sessions—on counselors’ emotional exhaustion and burnout levels. Results show how back-to-back, daily therapy sessions increased listening exhaustion levels and that counselors experienced both long-term and short-term listening exhaustion when utilizing telehealth due to lack of nonverbal cues and other related factors pertaining to online delivery. Implications for counselors, social workers, and other mental health professionals are discussed.